2012
DOI: 10.1051/0004-6361/201118184
|View full text |Cite
|
Sign up to set email alerts
|

New observations of chromospheric and prominence activity on the RS CVn-type binary SZ Piscium

Abstract: Aims. New high-resolution spectroscopic observations were made for the RS CVn-type binary SZ Psc aimed at searching for evidence of stellar prominences in this system and studying its chromospheric activity. Methods. By means of the spectral subtraction technique, we searched for prominence-like events in the H α spectra, and also analyzed several optical chromospheric activity indicators (the He i D 3 , Na i D 1 , D 2 , H α , and Ca ii IRT lines) included in our observations. Results. The emission in the H α … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…We obtain the chromospheric contribution in these activity indicators with the spectral subtraction technique by using the popular program STARMOD (Barden 1985;Montes et al 1995cMontes et al , 1997Montes et al , 2000. This technique has been widely and successfully used for chromospheric activity studies (e.g., Montes et al 1995cMontes et al , 1997Montes et al , 2000Gu et al 2002;Frasca et al 2008a;Zhang & Gu 2008;Cao & Gu 2012, 2014, 2015Zhang et al 2016). Although a spectral line from the third star has been found in the UX Ari spectrum, the contribution of the lines is very weak.…”
Section: Spectral Subtraction and Resultsmentioning
confidence: 99%
“…We obtain the chromospheric contribution in these activity indicators with the spectral subtraction technique by using the popular program STARMOD (Barden 1985;Montes et al 1995cMontes et al , 1997Montes et al , 2000. This technique has been widely and successfully used for chromospheric activity studies (e.g., Montes et al 1995cMontes et al , 1997Montes et al , 2000Gu et al 2002;Frasca et al 2008a;Zhang & Gu 2008;Cao & Gu 2012, 2014, 2015Zhang et al 2016). Although a spectral line from the third star has been found in the UX Ari spectrum, the contribution of the lines is very weak.…”
Section: Spectral Subtraction and Resultsmentioning
confidence: 99%
“…These images revealed that the K1 IV star exhibits pronounced high-latitude spots as well as numerous intermediate-and low-latitude spot groups during the entire observing season. High level of chromospheric activity associated with the K1 IV primary component was also demonstrated by strong chromospheric emission in Mg ii h & k, Ca ii H & K, Hα, and Ca ii infrared-triplet lines (e.g., Jakate et al 1976;Bopp et al 1981;Zhang & Gu 2008;Cao & Gu 2012). Hα outbursts and flare like events were detected by Bopp et al (1981), Ramsey & Nations (1981), and Huenemoerder & Ramsey (1984).…”
Section: Introductionmentioning
confidence: 90%
“…The authors also found variation in Mg ii strength, possibly phase-dependent, and an apparent eclipse of a plage in Mg ii. However, excess absorption features in the subtracted Hα profiles caused by prominence-like material have been discussed by Zhang & Gu (2008) and Cao & Gu (2012). Several optical chromospheric activity indicators were analyzed by Cao et al (2019) using the spectral subtraction technique, and during their observation, a series of possibly associated magnetic activity phenomena, including flare-related prominence activation, optical flare, and post-flare loops, were detected.…”
Section: Introductionmentioning
confidence: 99%
“…They found EW 8542 /EW 8498 ratios of 1.0-1.7, which implies the presence of optically thick plages. This is typical of many late-type stars [111,[122][123][124][125][126]. The infrared triplet lines are formed in the lower chromosphere through subordinate transitions between the excited levels of Ca II 4 2 P 1/2,2/3 and meta-stable 3 2 D 3/2,5/2 [127,128].…”
Section: Spectroscopic Diagnosticsmentioning
confidence: 98%